Pieter Bruegel the Elder and religion - Kaschek, Bertram; Müller, Jürgen, 1961-; Buskirk, Jessica (Brill's studies in intellectual history, 2018)
The book offers new insight into the religious dimension of Bruegel's art. With a number of highly original and thorough case studies, the volume illuminates Bruegel's inventive and multifaceted engagement with the contemporary religious concepts and practices of his day and age. Religion remains a vital question in the life and career of Bruegel, because it was so long believed to be more or less absent from his work. As a pioneer of the new genres of landscape and peasant scenes, Bruegel was heralded as a ground-breaking secular painter. This volume highlights the most recent scholarship on the artist, offering a much more nuanced portrait of Bruegel's engagement with the dynamic religious landscape of the mid-sixteenth century.